Early land plants: Plentiful but neglected nutritional resources for herbivores?. Issue 12 (12th December 2022) - Duhin, Audrey; Machado, Ricardo A. R.; Turlings, Ted C. J.; Röder, Gregory
Abstract: Plants and herbivores have been engaged in a co‐evolutionary arms race for millions of years, during which plants evolved various defenses and other traits to cope with herbivores, whereas herbivores evolved traits to overcome the plants' resistance strategies. Herbivores may also avoid certain plants merely because these lack suitable nutrients for their development. Interestingly, the number of herbivores that attack individual early land plants like mosses and ferns is quite low. Among others, poor nutrient quality has been hypothesized to explain the apparent low herbivory pressure on such plants but still waits for scientific evidences. Here, the nutritive suitability of representative mosses and liverworts (bryophytes) and ferns (pteridophytes) for herbivores was investigated using feeding assays combined with quantifications of nutrients (proteins, amino acids, and sugars). Growth and survival of two polyphagous herbivores, a caterpillar and a snail, were monitored when fed on 15 species of bryophytes and pteridophytes, as well as on maize ( Zea mays, angiosperm) used as an external indicative nutritional resource. Overall, our results show that the poor performance of the herbivores on the studied early land plants is not correlated with nutritional quality. The growth and performance of snails and caterpillars fed with these plants were highly variable and independent of nutrient content. These findings arguably dismiss the poor nutrient quality hypothesis as the cause of herbivory deficit in bryophytes and pteridophytes. They suggest the possible presence of early resistance traits that have persisted all through the long evolutionary history of plant–herbivore interactions. Abstract : In this paper, we explore the unknown reason(s) why herbivores rarely seem to attack early land plants like mosses and ferns. Our study, in which we looked at the performance of an arthropod and a gastropod on 15 species of such plants, yields surprising results that disqualify some of the common notions about early land plants.